2020
DOI: 10.1002/jdd.12506
|View full text |Cite
|
Sign up to set email alerts
|

Measurable reflection in simulation: A pilot study

Abstract: Purpose Debriefing is considered a cornerstone in the success of simulated learning practices. For debriefing to be productive and meaningful, reflection of the learners is essential. Measuring reflection during debriefing has proven to be difficult. This study aimed to validate a reflection rubric based on Kolb's Theory of Experiential Learning and integrate the assessment tool into simulation debriefing practice. Methods This research was a non‐experimental mixed‐methods, sequential explanatory design. Valid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Simulation is a technique that imitates real-life situations. It is utilised in several contexts, such as an educational process for students to implement learned skills and re-enact performances before the actual delivery to the healthcare system [ 1 , 2 ]. After the simulation, a follow-up procedure is needed for the reflective process of the students⁠ through debriefing procedures.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Simulation is a technique that imitates real-life situations. It is utilised in several contexts, such as an educational process for students to implement learned skills and re-enact performances before the actual delivery to the healthcare system [ 1 , 2 ]. After the simulation, a follow-up procedure is needed for the reflective process of the students⁠ through debriefing procedures.…”
Section: Introductionmentioning
confidence: 99%
“…After the simulation, a follow-up procedure is needed for the reflective process of the students⁠ through debriefing procedures. Students can reflect, contemplate, and associate their physical performances during the simulation to fully grasp the cognitive interpretation of the scenario during the debriefing process [ 2 , 3 ]. Generally, a debriefing conducted right after a simulation scenario is more effective than one during the simulation in terms of knowledge and confidence [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Lefroy et al reported the use of video-assisted reflection using realist methodology to improve students' ability to self-reflect ( 23 ). Other types of studies focused on validating rubrics for the purposes of evaluating the quality and depth of students' reflections ( 17 , 24 ). There was however a lack of studies to investigate the correlates, motivating factors and barriers to conducting regular self-reflection from the students' perspective.…”
Section: Introductionmentioning
confidence: 99%